Effects of Intrinsic and Extrinsic Quality Cues and Perceived Risk on Visitors’ Satisfaction and Loyalty - Hossain, M.E.; Quaddus, Mohammed; Shanka, Tekle (Taylor & Francis Group, 2015)
This empirical study was conducted to explore the effects of intrinsic and extrinsic quality cues on different causal relationships of risk on visitors’ satisfaction and loyalty at the tourism destination level. In total, 602 samples were collected from Cox’s Bazar, Bangladesh using the six-point Likert Scale. The data were then analyzed using a partial least squares (PLS) based structural equation modeling (SEM) approach. The result strongly supports that quality cues have direct influence on satisfaction and satisfaction has a direct influence on loyalty. The theoretical and managerial implications are presented based on the study findings. Recommendations and future research directions are also proposed.